Diskursus Islam Nusantara dalam Representasi Media Massa - Fahmi, Muhammad (Jurnal Komunikasi Islam, 2017)
This study aims to look at how the representation of the Islam Nusantara in the national media in Indonesia, namely Kompas and Republika. The method used in this study is critical discourse analysis, Theo van Leeuwen, which focuses on how actors are represented in media texts both in the inclusion and the exclusion strategies. This study concludes that, first, Kompas tends to support the Islamic discourse of Nusantara, while Republika tend to reject the discourse. Further, Kompas represents the ideology of pluralism and nationalism, whilts Republika tends to present a contestation between the pros and cons of Islam Nusantara. Those who disagree with Islam Nusantara more represent the ideology of scrituralism, whilst those who pros of it tend to reflect traditionalist ideology.